Penerapan Pembelajaran STEM Berbasis Robotik S4A Arduino Untuk Meningkatkan STEM Teacher Identity Di SMAS Perintis Tanjung Jabung Timur: (Integrating Robotics-Based STEM Learning with S4A Arduino to Strengthen STEM Teacher Identity at SMAS Perintis Tanjung Jabung Timur) - Susanti, Nova; Aina, Mia; Sanova, Aulia; Dani, Rahma; Iriani, Dewi (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
Strengthening STEM literacy is essential in facing 21st-century challenges that demand critical thinking, creativity, collaboration, and technological literacy. However, the implementation of STEM education in Indonesia still faces obstacles, such as limited technological training for teachers and the lack of student experience in project-based learning. Therefore, this program was designed to provide hands-on and practical experiences through educational robotics.This community service program was conducted at SMAS Perintis Tanjung Jabung Timur with the aim of enhancing students’ STEM literacy and strengthening teachers’ identity as STEM educators (STEM Teacher Identity) through robotics-based learning using the S4A Arduino platform. The implementation method included workshops, hands-on robot programming sessions, mini-project mentoring, and reflective learning activities. A total of 25 students and several teachers actively participated in the program. The evaluation results indicated that more than 85% of participants responded positively, Students stated that learning using S4A Arduino robotics was engaging and relevant to their everyday lives. Approximately 70% of Students successfully completed robotics projects that demonstrated a good understanding of how Arduino components work and function. Despite challenges such as limited tools and time, this program proved effective and relevant. Overall, the activity successfully enhanced 21st-century skills, strengthened teachers’ pedagogical competence, and showed potential for replication in other schools as a support to the STEM curriculum and the Merdeka Belajar (Freedom to Learn) policy. Abstrak. literasi STEM menjadi penting dalam menghadapi tantangan abad ke-21 yang menuntut kemampuan berpikir kritis, kreatif, kolaboratif, dan melek teknologi. Namun, pelaksanaan pendidikan STEM di Indonesia masih menghadapi keterbatasan, seperti kurangnya pelatihan teknologi bagi guru dan minimnya pengalaman siswa dalam pembelajaran berbasis proyek. Oleh karena itu, kegiatan ini dirancang untuk memberikan pengalaman langsung dan aplikatif melalui robotika edukatif. Kegiatan pengabdian kepada masyarakat ini dilaksanakan di SMAS Perintis Tanjung Jabung Timur untuk meningkatkan literasi STEM siswa serta memperkuat identitas guru sebagai pendidik STEM (STEM Teacher Identity) melalui pembelajaran berbasis robotik menggunakan platform S4A Arduino. Metode pelaksanaan meliputi workshop, praktik hands-on pemrograman robot, pendampingan proyek mini, serta refleksi pembelajaran. Sebanyak 25 siswa dan beberapa guru berpartisipasi aktif dalam kegiatan ini. Hasil evaluasi menunjukkan lebih dari 85% peserta memberikan respons positif siswa menyatakan bahwa pembelajaran menggunakan robotik S4A Arduino menarik dan relevan dengan kehidupan mereka sehari-hari. Sekitar 70% siswa berhasil menyelesaikan proyek robotik yang menunjukkan pemahaman yang baik tentang cara kerja dan fungsi komponen Arduino. Meskipun terdapat kendala berupa keterbatasan alat dan waktu, kegiatan ini terbukti efektif dan relevan. Secara keseluruhan, program ini berhasil memperkuat keterampilan abad ke-21, meningkatkan kompetensi guru, dan berpotensi direplikasi di sekolah lain sebagai dukungan terhadap kurikulum STEM dan kebijakan Merdeka Belajar.